An Impact of CSR Program in Enhancing Welfare (A Case Study of Catfish Cultivation Group Tanah Berongga-Sido Urep Kebun Tanjung Seumantoh Village, Karang Baru Sub District Aceh Tamiang District, Aceh Province) - Baihaqi; Zulkarnen Mora; Abdul Latief (Jurnal Ilmiah Samudra Akuatika, 2020)
Corporate Social Responsibilities was part of fully commitment from the company to communities. This responsibility applied into CSR policy aims to increase sensibility and occuring positive impact for the company. The principle of CSR implemented by PT Pertamina EP-Field Rantau refers to five essentials: local resources based, community based, economic empowerment, sustainability and participatory planning. Act number 25 tahun 2007 about capital investment and Act number 40 tahun 2007 about limited company mentions for tripple buttom line. In 2010 PT Pertamina EP-Field Rantau has conducted social mapping to Makmur Sub-village. The result indicated that the villagers are living in poverty line and teenegers were not working well. The main prospect developed were fishery cultivation due to the topography of this sub village were clay and preferable for ground pool and the availability of natural feeds like golden snail and maggot. PT Pertamina EP-Field Rantau committed to establish group of cultivation of catfish Tanah Berongga-Sido Urep. PT Pertamina EP-Field Rantau assisted technical assistance through local partnership. This strategy sychronizes with MDG‘s goal in establishing global partnership in order to decrease poverty. There were 8 members previously and now 24 members joining to this group. The method was used case study whereas this was identical with explanatory by attracting causality for the object. The advance accepted by group of cultivation of catfish Tanah Berongga-Sido Urep appreciated from local and national media. The massive news was influenced to the rapidly of visitor with aiming to study, comparative study and recreation. Currently each of members was getting profitable 6 millions/ depends on the amount of catfish pool owned. This effort shown that catfish cultivation was giving significant impact for these groups and the desire to create Makmur Sub-village as a center of catfish cultivation in Aceh Tamiang.